Control of immune pathology by regulatory T cells. - Powrie, F; Read, S; Mottet, C; Uhlig, H; Maloy, K (2003)
CD4+CD25+ T(reg) cells inhibit colitis in the severe combined immune deficient (SCID) T cell adoptive transfer model. Cells with this function are present in the thymus suggesting that T(reg) cells capable of inhibiting bacteria-induced immune pathology are similar to those that inhibit organ-specific autoimmunity. CD4+CD25+ T(reg) cells inhibit both T cell-dependent and T cell-independent intestinal inflammation. The latter point illustrates that in addition to direct effects on other T cells, T(reg) cells can alsoprevent immune pathology in vivo by inhibiting the actions of innate immune cells. T(reg) cells suppress intestinal inflammation through mechanisms that involve interleukin 10 and transforming growth factor beta and blockade of the negative regulator of T cell activation CTLA4 abrogates T(reg) cell function in vivo. Importantly adoptive transfer of CD4+CD25+ T(reg) cells to mice with established colitis reverses inflammation and restores normal intestinal architecture suggesting that CD4+CD25+ T(reg) cells may be utilized for cellular therapy of inflammatory diseases.